Color Removal From Synthetic Textile Wastewater Using a Pilot-Scale Anaerobic Bioreactor - Cemanovic, Amar; Arikan, Osman Atilla; Cinar, Ozer (Mehmet Sinan Bilgili, 2022)
The textile industry is notorious for the high volume of wastewater it produces. Depending on the process, it may be high in organic matter, acids/bases, strong chemicals, or have significant concentrations of dye. The latter is an inevitable consequence of textile dyeing processes that happens because of the relatively low dye retention of fabrics. Physicochemical processes such as ozonation and coagulation are efficient in removing color from wastewater but are not the most cost-effective and environmentally friendly approaches. As an alternative, various biological methods have been examined - most prominently anaerobic processes. The nature of anaerobic bacterial digestion provides for a way to utilize the dye as an electron acceptor, thereby metabolizing it into simpler and less harmful compounds. In this study, a pilot-scale anaerobic CSTR bioreactor was operated with synthetic textile wastewater, and the efficiency of COD and color removal was evaluated. The results suggest that such systems are effective in removing most of the COD and color from the wastewater. In addition, relevant literature suggests that coupling anaerobic with aerobic reactors in one system could provide the best removal efficiencies for this type of wastewater. Further research is required to evaluate this approach in pilot-scale and full-scale systems.
Keywords: Color removal; textile wastewater; biological treatment; anaerobic bioreactors; Engineering; Environmental Sciences & Ecology